TRANSFORMASI UMKM BERBASIS ISLAMIC SOCIOPRENEUR MENUJU DIGITALISASI DAN GLOBALISASI PADA UMKM DESA WARNASARI, KABUPATEN BANDUNG - Pramayanti, Dian Ikha; Fazriah, Siti; Sari, Eko Gumaya; Zikri, Arian; Ali, Kurnia Fatimah (JURNAL ABDIMAS PLJ, 2025)
This community service activity is carried out to assist and empower the concept of islamic sociopreneurship in warnasari village, bandung regency. This activity aims to improve the ability of UMKM actors tomanage businesses based on islamic value by utilizing digitalization to increase competitiveness and global market reach. Islamic sociopreneurship is a business that is rum with sharia principles that aim to improve community welfare and provide benefits to the surrounding environment. From this acivity, it is hoped that it can create a positive social impact and the approach through islamic sociopreneurship can be an effective solution. With the digitalization of UMKM, UMKM actors have carried out a transformation process from traditional methods to digital technology that can help increase competitiveness and increase wider market reach.